GAMBARAN KESESUAIAN JENIS ALAT PERMAINAN UNTUK STIMULASI PERKEMBANGAN PADA ANAK USIA TODDLER - Friska Oktonamara; Ganis Indriati; Bayhakki Bayhakki (Fakultas Keperawatan, Universitas Riau, 2023)
Toys are one of the tools for playing that can stimulate children's development according to their age and level of development. The aim of this research was to describe the suitability toy for developmental stimulation in toddler. The study was descriptive research. The sample was 53 parents whose have toddler, that selected by purposive sampling techniques and considered into the inclusion criteria. The measuring instrument used is a questionnaire sheet about the suitability of type toys that had been testing for validity and reability. The data has been analyzed using descriptive test. The result showed, most respondents were aged 20 – 40 years (89.8%), girl (93.2%), had high school education (55.9%). Respondents on average were a housewive who did not work (59.3%), were Malay (44.1%), and family income above the city’s minimum income (79.2%), The majority of respondent’s children were in the age 25-36 months (54.2%), and were male (59.3%). The toys used to stimulate the developmental of toddlers are in the appropriate category (61%), in the terms of safety, size, design and function. This research expected that parents will know and be able to provide appropriate toy to stimulate the development of toddler-aged children.